ELECTROMAGNETIC WAVE'S REFLECTION AND REFRACTION ON A TWO-LAYER MAGNETIC STRUCTURE (Web of Teachers: Inderscience Research, 2024)
In the study of nanostructures, the study of multilayer magnetic structures is of great importance. In this paper, we will consider a two-layer magnetic structure, the first layer of which is a film with a thickness ℓ magnetized in equatorial geometry, and the second layer is a substrate magnetized in polar geometry.